THE EFFECTIVENESS OF WORK-INTEGRATED LEARNING IN DEVELOPING ECONOMICS EDUCATION STUDENT TEACHERS' PEDAGOGICAL AND SUBJECT MATTER EXPERTISE (International Journal of Innovative Technologies in Economy, 2024)
Work-integrated learning (WIL) has gained prominence in teacher education, particularly in economics education. WIL, which involves integrating theoretical knowledge with practical experience in real-world settings, has gained prominence in teacher education as a means of enhancing student teachers' readiness for the profession This literature review synthesis investigates the effectiveness of WIL in developing economics education student teachers' pedagogical and subject matter expertise. The study followed the systematic literature review method PRISMA in selecting studies to be included and excluded in the synthesis of the study. The process commenced by identifying the problem and screening studies to include and exclude in the study. Only 14 studies conducted between 2020 and 2024 were screened for inclusion. The findings reveal that WIL significantly improves teaching confidence, classroom management, lesson planning and delivery, and assessment and feedback skills. The findings also revealed that WIL significantly enhances content knowledge, conceptual understanding, application and analysis, critical thinking and problem-solving. The study's findings have significant implications for teacher education policy and practice. However, the study is limited by potential interpretive bias, lack of methodological triangulation, and unexplored alternative explanations. Language restrictions, limited database access, and financial constraints further circumscribe its scope and depth. These limitations may have excluded relevant research or perspectives, impacting the study's reliability and validity. Educators, policymakers, and researchers must prioritize WIL's potential in developing pedagogical and subject matter expertise. Future research should investigate WIL's long-term impact on teacher development and student learning outcomes.